The DEAR-COTS hard real-time subsystem - Pinho, Luís Miguel (2000)
In this report, the Hard Real-Time Subsystem of DEAR-COTS is described, and the services it must provide are identified. This report is an input of ISEP/IPP and FEUP for the specification of the DEAR-COTS architecture (deliverable to the FCT).